2021
DOI: 10.3390/antiox10071154
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Oxidative Stress on Male Reproduction in Domestic and Wild Animals

Abstract: Oxidative stress occurs when the levels of reactive oxygen species (ROS) overcome the antioxidant defenses of the organism, jeopardizing several biological functions, including reproduction. In the male reproductive system, oxidative stress not only impairs sperm fertility but also compromises offspring health and survival, inducing oxidative damage to lipids, proteins and nucleic acids. Although a clear link between oxidative stress and male fertility disorders has been demonstrated in humans and laboratory r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 198 publications
1
48
0
Order By: Relevance
“…Mounting evidence suggests H 2 O 2 as one of the major ROS generating chemical attacking several components of cells such as proteins, lipids and DNA causing potential oxidative insults (Shi et al. 2018 ; Pintus and Ros-Santaella 2021 ). H 2 O 2 produced excessive reactive hydroxyl radicals are cytotoxic causing sperm kinematic alternations such as declined motility, progression and reduced spermatozoa energy metabolism (Shi et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mounting evidence suggests H 2 O 2 as one of the major ROS generating chemical attacking several components of cells such as proteins, lipids and DNA causing potential oxidative insults (Shi et al. 2018 ; Pintus and Ros-Santaella 2021 ). H 2 O 2 produced excessive reactive hydroxyl radicals are cytotoxic causing sperm kinematic alternations such as declined motility, progression and reduced spermatozoa energy metabolism (Shi et al.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that exogenous treatment of H 2 O 2 has been shown to increase intracellular ROS levels in male reproductive cells (Shi et al. 2018 ; Pintus and Ros-Santaella 2021 ). Further, the mouse TM3 Leydig cell lines were well used as a valuable in vitro model to study the spermatogenic parameters induced by various cytotoxins including H 2 O 2 (Ding et al.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a greater proportion of spermatozoa with alterations to the membranous structures and morphological defects has been found in ejaculates contaminated with bacteria [ 9 , 10 , 11 , 12 ]. At the same time, it has been reported that bacteriospermia may induce an imbalance in the seminal oxidative balance, by accelerating reactive oxygen species (ROS) overproduction [ 13 ], an excessive release of pro-inflammatory cytokines, and subsequent damage to the sperm structures crucial for the male gamete to reach the oocyte and successfully accomplish fertilization [ 10 , 14 ]. Ultimately, bacteriospermia may be responsible for reduced shelf life of extended or cryopreserved semen samples [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…An increase in MDA levels and a decrease in SOD indicated oxidative stress followed by cell death mechanisms, such as apoptosis or necrosis [ 53 ]. Administration of α -tocopherol started from a dose of 77 and 140 mg per kg BW, returning MDA levels and SOD activity to those of normal rats.…”
Section: Discussionmentioning
confidence: 99%